Pretreatmet with 5% lidocaine patch reduces cannula-induced and propofol-induced pain: a randomized, double-blind, placebo-controlled study - Hong, Jung-Min; Lee, Hyeon Jeong; Cho, Ah Reum; Baik, Ji Seok; Lee, Do Won; Ji, Young Tae; Yoo, Ki Chan; Kim, Hae-Kyu (Korean journal of anesthesiology, 2016)
The purpose of this study was to determine the efficacy of 5% lidocaine patch in reducing propofol-induced pain and cannula-induced pain. In a randomized, double-blind study, 126 patients were divided into one of three groups: pretreatment with a 5% lidocaine patch (Lidotop®) and premixed 2 ml of normal saline with 1.5 mg/kg of 1% propofol (Group A); pretreatment with a placebo patch and premixed 2 ml of normal saline with 1.5 mg/kg of 1% propofol (Group B); or pretreatment with a placebo patch and premixed 2 ml of 2% lidocaine (40 mg) with 1.5 mg/kg of 1% propofol (Group C) for induction of anesthesia. Pain severity was evaluated on a four-point verbal rating scale during intravenous cannulation, propofol injection, and 24 h after the operation (recall). Eighteen patients (47.4%) in Group A complained of cannula-induced pain compared with 35 (94.6%) in Group B and 36 (94.7%) in Group C (P < 0.001). Group A patients showed significantly lower incidence of propofol-induced pain and recall of propofol-induced pain compared with Group B (P < 0.001 and P = 0.01), whereas there was no difference compared with Group C. Preoperative transdermal administration of 5% lidocaine patch is an effective and simple method in reducing propofol-induced pain as well as cannula-induced pain.